A novel study on preparation of H2TiO3–lithium adsorbent with titanyl sulfate as titanium source by inorganic precipitation–peptization method. Issue 3 (3rd January 2018) - Zhang, Li-Yuan; Liu, Yi-Wu; Huang, Lan; Li, Ning
Abstract : A peroxy Li2 TiO3 sol was prepared with low-cost TiOSO4 as titanium source, CH3 COOLi as lithium source, and H2 O2 as complexing agent by inorganic precipitation–peptization method. Abstract : A peroxy lithium titanate sol was prepared with low-cost and easily available titanyl sulfate as the titanium source, lithium acetate as the lithium source, and aquae hydrogenii dioxidi as the complexing agent using an inorganic precipitation–peptization method. The sol system was aged, centrifugal-washed, dried and calcined to obtain a pure precursor, Li2 TiO3, followed by pickling with hydrochloric acid to obtain the H2 TiO3 –lithium adsorbent. The effects of aging time and calcination temperature on the target product were investigated. The results indicate that the sol-system is stable, which is beneficial for loading on a suitable carrier, such as ceramic foams. Centrifugal-washing, instead of vacuum filtration-washing, is conducive to product formation. The most suitable aging time of precursor sol is 24 h and the appropriate calcination temperature is 750 °C. The lithium drawn-out ratio of samples synthesized in this condition reaches 89.50% after pickling with 0.2 M hydrochloric acid for 8 h at 70 °C. Moreover, the Li + uptake of the adsorbent (adsorption capacity) reaches 29.96 mg g −1 and 33.35 mg g −1 when the adsorption time is 1 h and 8 h, respectively.